Generating Sharp Panoramas from Motion-blurred Videos - Li, Yunpeng; Kang, Sing Bing; Joshi, Neel; Seitz, Steve; Huttenlocher, Daniel (Computer Vision and Pattern Recognition (CVPR), 2010 IEEE Conference on, 2010)
In this paper, we show how to generate a sharp panorama from a set of motion-blurred video frames. Our technique is based on joint global motion estimation and multi-frame deblurring. It also automatically computes the duty cycle of the video, namely the percentage of time between frames that is actually exposure time. The duty cycle is necessary for allowing the blur kernels to be accurately extracted and then removed. We demonstrate our technique on a number of videos